Causes of construction delay from contractors and suppliers in Thailand's oil and gas platform projects - Pittayaporn Gomarn; Jakrapong Pongpeng (My University, 2018)
Construction project delays caused by contractors and suppliers are the top problems in Thailand's oil and gas industries. Recognizing this importance and their relationships between factors can help reduce the risk of delays in construction projects. Therefore, this study set out to confirm factors and inspect relationships between delay factors of contractors and suppliers. A 16 item questionnaire survey was distributed to 134 managers, engineers, and supervisors in oil and gas platform construction projects in Thailand. A confirmatory factor analysis (CFA) was performed by the use of Amos Version 20 software program. The analysis results showed that delays caused by the contractors and suppliers had high relationships, due to high regression weighs. The delays caused by the contractors included seven factors which included poor site management and supervision (17%), lack of safety rules and regulations (16%), poor communication and coordination with others (15%), poor procurement system management (15%), defective components and mistakes during construction (14%), supplier payments lateness (13%), and poor planning and scheduling (10%). The delays caused by the suppliers included six factors which included the supply of unqualified and unskilled personnel (22%), supply of low efficiency equipment (20%), late delivery of materials and equipment (20%), supply of low quality materials (16%), late supply of workers (16%), and price escalation (5%).
Keywords: Construction Project Management and Performance